Blockchain for Social Good: A Case Study on the Use of Distributed Ledger Technology for Transparent Supply Chains in Fair Trade Coffee - Shahram Rahimov; Dilshod Tursunov; Gulbahor Alimova (Journal of Social Science Utilizing Technology, 2025)
Background. The increasing demand for transparency in global supply chains has prompted the exploration of emerging technologies such as blockchain. In particular, the application of distributed ledger technology (DLT) in fair trade industries has the potential to enhance accountability, traceability, and ethical sourcing practices. This study examines the use of blockchain in the fair trade coffee sector, where transparency is crucial to ensure that producers receive fair compensation and consumers can trust the authenticity of ethical claims. Purpose. The primary aim of this research is to investigate how blockchain technology can improve transparency and efficiency in the coffee supply chain, from farm to consumer. Method. The study employs a case study methodology, focusing on a fair trade coffee cooperative that implemented blockchain to track the journey of coffee beans. Qualitative interviews with stakeholders, including farmers, distributors, and consumers, were conducted to gather insights into the practical applications and challenges of blockchain in this context. Results. The findings indicate that blockchain enhances transparency by providing immutable records of transactions, but challenges related to technology adoption, cost, and scalability remain. Conclusion. The study concludes that while blockchain shows promise for social good in fair trade coffee, further research and development are needed to address the limitations and expand its implementation across the industry.